Drivers and Impacts of Agricultural Land Conversion: Regression Modelling with Spatial Dependence in West Bandung and Purwakarta Regencies, Indonesia - Wijayanto, Arie Wahyu; Prasetyo, Rindang Bangun; Putri, Salwa Rizqina; Sugiarto, Sugiarto; Marsisno, Waris; Wahyuni, Krismanti Tri; Pasaribu, Ernawati; Maghfiroh, Meilinda F N (UIN Sumatera Utara, 2025)
The rapid conversion of farmland to non-agricultural uses in West Java threatens food security, farmer livelihoods, and environmental sustainability. This study investigates the causes and consequences of land conversion in West Bandung and Purwakarta Regencies using a mixed-source data, including geotagging, CAPI, and secondary data from satellite images, focusing on landowners who converted farmland between 2013 and 2021. Multiple linear regression and spatial models, including Spatial Lag Model (SLM), were applied to assess key determinants. The results revealed economic pressures as the main driver, with rice fields most affected and various geographic and infrastructure factors influencing outcomes. The findings underscore the need for targeted policies to balance development with sustainable land and food system management.